Управленческое партнерство в стратегии развития Российской библиотечной ассоциации (Библиосфера)
The article discusses the urgent problem of democratization in the management of the library social institution, stated by the Russian Library Association in the «Priorities of Development» for 2011-2015. The author examines different types of partnership relations between public and state institutions and introduces the concept «management partnership». The priorities facing the government and civil structures on forming public policy in the field of library activity are formulated.